2013
DOI: 10.2337/dc12-1912
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Protein Versus High-Carbohydrate Diets on Markers of β-Cell Function, Oxidative Stress, Lipid Peroxidation, Proinflammatory Cytokines, and Adipokines in Obese, Premenopausal Women Without Diabetes

Abstract: OBJECTIVETo study the effects of high-protein versus high-carbohydrate diets on various metabolic end points (glucoregulation, oxidative stress [dichlorofluorescein], lipid peroxidation [malondialdehyde], proinflammatory cytokines [tumor necrosis factor-α and interleukin-6], adipokines, and resting energy expenditure [REE]) with high protein–low carbohydrate (HP) and high carbohydrate–low protein (HC) diets at baseline and after 6 months of dietary intervention.RESEARCH DESIGN AND METHODSWe recruited obese, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
3
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 35 publications
4
75
3
3
Order By: Relevance
“…4 on weight control, cardiovascular parameters, and adipokine levels (9)(10), similar to those of the Mediterranean diet (11,(12)(13)(14)(15), although the association has been less clear in studies of high-carbohydrate diets (16)(17)(18).…”
Section: Accepted Manuscriptmentioning
confidence: 82%
“…4 on weight control, cardiovascular parameters, and adipokine levels (9)(10), similar to those of the Mediterranean diet (11,(12)(13)(14)(15), although the association has been less clear in studies of high-carbohydrate diets (16)(17)(18).…”
Section: Accepted Manuscriptmentioning
confidence: 82%
“…The increased adiponectin levels in the PD group may relate to weight loss, with increased protein intake as a contributing factor [44,45]. The unaltered hormone levels in the PD-EX group may indicate the increased plasma volume because of physical activity [46].…”
Section: Discussionmentioning
confidence: 99%
“…Body composition, LM composition, FM, and bone mineral content were assessed. 7 The DXA Quality Assurance manual for the GCRC was used to standardize patient positioning and scan analysis.…”
Section: Methodsmentioning
confidence: 99%
“…26 Another important aspect of a HP diet is the antiinflammatory effect and decreased glucose area under the curve (AUC) compared with a HC diet as was shown in our previous study. 7 Other studies have demonstrated that hyperglycemia during glucose challenge or elevation of FFA 27 leads to activation of leukocytes and reactive oxygen species (ROS). We have also shown that hyperglycemia in vivo and in vitro activates T cells, increases inflammatory cytokines, lipid peroxidation, and ROS.…”
Section: Significance Of This Studymentioning
confidence: 99%